2016
DOI: 10.1353/csd.2016.0007
|View full text |Cite
|
Sign up to set email alerts
|

Drinking and Dating: Examining the Link Among Relationship Satisfaction, Hazardous Drinking, and Readiness-to-Change in College Dating Relationships

Abstract: The present study examined the influence of relationship satisfaction on readiness-to-change alcohol use and the influence of hazardous drinking on readiness-to-change relationship issues in college student dating relationships. A sample of 219 college students in a current dating relationship (aged 18–25) completed self-report measures of dating relationship satisfaction, alcohol use, readiness-to-change alcohol use, and readiness-to-change relationship issues via an online survey from August to December 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 72 publications
2
5
0
1
Order By: Relevance
“…Results indicated that single individuals and those in casual relationships reported a higher percentage of personal alcohol use during sexual situations within the past year compared with those in committed relationships. These findings converge with previous research that suggests that involvement in committed relationships serves as a protective factor against maladaptive health behaviors, such as alcohol use (e.g., Khaddouma et al, 2016; R. G. Thompson et al, 2014;Whitton et al, 2013). These findings should be understood in the context in which this study was conducted.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results indicated that single individuals and those in casual relationships reported a higher percentage of personal alcohol use during sexual situations within the past year compared with those in committed relationships. These findings converge with previous research that suggests that involvement in committed relationships serves as a protective factor against maladaptive health behaviors, such as alcohol use (e.g., Khaddouma et al, 2016; R. G. Thompson et al, 2014;Whitton et al, 2013). These findings should be understood in the context in which this study was conducted.…”
Section: Discussionsupporting
confidence: 90%
“…However, a socialization effect may also occur, such that romantic partners can also motivate each other to engage in healthy behaviors, particularly those that can benefit the relationship. For instance, risky drug and alcohol use can negatively affect interactions between romantic partners, perhaps motivating each to reduce unhealthy behaviors to improve their relationship quality (Duncan, Wilkerson, & England, 2006; Khaddouma et al, 2016; Lewis & Butterfield, 2007). High-quality romantic relationships in and of themselves also provide mutual intimacy and support, which are vital to well adjustment in individual development particularly for emerging adults—the developmental period between 18 and 25 years (Arnett, 2004).…”
Section: Theoretical Framework For the Present Studymentioning
confidence: 99%
“…Findings on association between third year of study and drug use are comparable to an eight year longitudinal analysis in Mid-Atlantic that reported highest annual peak of marijuana use in year three of study (8). This could be attributed to factors like academic-related stress (24), poor social skills thus increased vulnerability to peer pressure to use drugs (25), limited physical activities (26) and poor quality dating relationships (27). All the aforementioned factors combined increased vulnerability to stress and depression which in turn heightens drug use as a form of self medication.…”
Section: Discussionsupporting
confidence: 52%
“…Individu yang merasa puas dengan hubungannya atau merasakan relationship satisfaction akan memiliki kesehatan mental yang lebih baik, lebih siap dalam menghadapi masa depan dan memiliki kesiapan yang tinggi untuk mengubah perilaku buruk menjadi lebih baik demi pasangannya (Khaddaouma et al, 2016). Selain itu, individu yang merasakan relationship satisfaction akan merasakan konteks hidup secara positif dan memberikan manfaat bagi kesehatan mental yang berupa adanya kebahagiaan dan kesehatan fisik (Whisman, Uebelacker, & Settles, 2010).…”
Section: Pendahuluanunclassified